THE EFFECT OF COAL MINING ACTIVITIES ON HYDROLOGICAL PARAMETER CHANGE - Hasan, Harjuni; Sarwono, Edhi (Jurnal Chemurgy, 2024)
Mining is a conventional activity that alters the natural landscape and causes hydrological parameter changes and environmental disruptions, such as hampered vegetation growth due to water table subsidence, damaged productive land that affects the river flow, water pollution, deforestation, and erosion. Land clearing for coal mining activity potentially damages the soil layer structure, due to the loss of ground cover vegetation, so hydrological parameter changes, including an 11.79% (50.55 mm) decreased base flow, 40.35% (273.73 mm) increased direct runoff, 21.92% (250.30 mm) increased surface runoff, an 15.73% (76.21 mm) decreased infiltration, 11.03 % (122.52 mm) increased potential evapotranspiration, causing fluctuating river debit. Every 10 Ha of land clearing for mining activities related to 51.46% (291.36 mm) increased runoff. Meanwhile, the postmining activities, including reclamation and vegetation, could only decrease the baseflow by 6.95% (5.95 mm) while increasing the direct runoff, surface runoff, infiltration, and potential evapotranspiration by 9.36% (89.11 mm), 11.19% (148.20 mm), 3.81% (15.56 mm), and 1.73% (21.34 mm), respectively. Furthermore, every 10 Ha of reclamation area is related to an 47.22% (264.62 mm) decrease in runoff.